2014
DOI: 10.1016/j.irle.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous decentralization in federal environmental policies

Abstract: Under most federal environmental laws and some health and safety laws, states may apply for "primacy," that is, authority to implement and enforce federal law, through a process known as "authorization." Some observers fear that states use authorization to adopt more lax policies in a regulatory "race to the bottom." This paper presents a simple model of the interaction between the federal and state governments in such a scheme of partial decentralization. Our model suggests that the authorization option may n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Given this, scholars have observed two competing phenomena in state environmental programs: a "race-to-the-top" and a "race-to-the-bottom" (Chang, Sigman, and Traub 2014;Konisky 2007;Konisky and Woods 2010;Koski 2007;Potoski 2001;Woods 2006aWoods , 2006b. In terms of the former, some states are willing to exceed federal environmental standards to satisfy growing citizen demands for environmental quality.…”
Section: Environmental Federalismmentioning
confidence: 99%
“…Given this, scholars have observed two competing phenomena in state environmental programs: a "race-to-the-top" and a "race-to-the-bottom" (Chang, Sigman, and Traub 2014;Konisky 2007;Konisky and Woods 2010;Koski 2007;Potoski 2001;Woods 2006aWoods , 2006b. In terms of the former, some states are willing to exceed federal environmental standards to satisfy growing citizen demands for environmental quality.…”
Section: Environmental Federalismmentioning
confidence: 99%
“…Local authorities autonomously manage environmental affairs and often choose to relax environmental regulation for capital inflow, resulting in environmental degradation [20]. Others hold that local governments implement stringent environmental regulations as the degree of ED increases [21], which helps to reduce regional environmental pollution [22]. At present, in most studies of the environmental effects of ED [19], only a few considered the joint effects on the environment and economic growth [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of environmental decentralization, some researchers have argued that decentralization can decrease the efficiency of environmental policies [18] and increase environmental pollution [19] because when local authorities manage environmental affairs, they often choose to loosen environmental regulation for capital inflow, resulting in environmental degradation [20]. Others hold that local governments implement environmental regulations in a more stringent manner as the degree of environmental decentralization increases [21], which helps to reduce regional environmental pollution [22]. In effect, it is suggested that fiscal decentralization as a moderating variable can indirectly affect the effects of environmental regulations on environmental quality or economic growth [10,11].…”
Section: Literature Reviewmentioning
confidence: 99%